Transport and retention of nano emulsified vegetable oil in porous media: Effect of pore straining, roughness wedging, and interfacial effects. (15th October 2022) - He, Baonan; He, Jiangtao; Bi, Erping; Zou, Hua; Liu, Tao; Liu, Zirong
Abstract: Emulsified vegetable oil (EVO), as one of the novel green substrates, has been widely used in subsurface remediation. In these applications, the retention behavior of EVO presents a challenge to remediation efficiency as mechanism insights into the retention of EVO is limited. Herein, Brinell funnels experiments with X-ray microtomography (XMT) were conducted to examine the drainage and retention of nanoscale EVO in porous media, with a specific focus on investigating the impact of pore straining, grain surface roughness, and interfacial effects on Nano-EVO (NEVO) retention. This study demonstrated that the retention of NEVO in porous media is the synergistic result of pore straining, roughness wedging, and interface attachment. With the action of these effects, three residual states of NEVO, incorporating retention at porous ganglia, grain-grain contacts, and grain surface, were identified by XMT in porous media. After multiple periods of drainage and imbibition, the NEVO arrived at stable retention proportions of 46.3%, 72.2%, and 85.9% in three independent systems with coarse, medium, and fine sand as porous media, respectively. The interfacial effects, including the attachment of solid-phase and air-liquid interface, are confirmed as the dominant factors for the retention of NEVO in porous media, which contributed 35.63–47.33% of total retention for the conditions employed. Correspondingly, the contributions of pore straining and roughness wedging only ranged 3.78–24.06% and 3.87–9.94%, respectively. The consistency of the contributions between the actual measurement of XMT and computational evaluation further confirmed the rationality and reliability of the results. In such the dominant factor, interfacial tension, contact angle, and capillary radius play an essential role in NEVO retention, which could be reflected by capillary rise height. These findings advance our understanding on NEVO retention caused by substrate-media interaction and also offer a promising direction for subsurface remediation. Graphical abstract: Image 1 Highlights: Nano-emulsified vegetable oil retention states are successfully identified in geomedia. A synergistic mechanism is proposed for Nano-emulsified vegetable oil retention. Interfacial effects contributed most to Nano-emulsified vegetable oil retention. Interfacial tension, contact angle, and pore radius are vitally in interfacial effects.